2018
DOI: 10.4103/ccd.ccd_51_18
|View full text |Cite
|
Sign up to set email alerts
|

Association of human interleukin-35 level in gingival crevicular fluid and serum in periodontal health, disease, and after nonsurgical therapy: A comparative study

Abstract: Background:Innovating newer methods to diagnose a multifactorial disease such as periodontitis is always challenging for a clinician. Gingival crevicular fluid (GCF) which is closely associated with the periodontal tissue environment has been used a viable alternative to saliva for the diagnosis of periodontitis.Aim:The aim of the present study was to estimate and compare the interleukin-35 (IL-35) levels in GCF and serum among healthy, gingivitis, and chronic periodontitis (CP) individuals as well as to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…Many studies evaluated simultaneously different biomarkers in the gingival crevicular fluid (GCF) and in the bloodstream, based on the hypothesis that chronic periodontal inflammation induces a chronic systemic inflammatory status. In a recent study, in a cohort of 60 patients divided in three equal groups (healthy, gingivitis, and periodontitis), the concentration of GCF and serum interleukin (IL) 35 was found significantly higher in the periodontitis group (Raj et al, ). The same results were found for other inflammatory markers, such as visfatin, vascular endothelial growth factor (VEGF), oncostatin M, protein carbonyl, and tumor necrosis factor α (TNF‐α).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies evaluated simultaneously different biomarkers in the gingival crevicular fluid (GCF) and in the bloodstream, based on the hypothesis that chronic periodontal inflammation induces a chronic systemic inflammatory status. In a recent study, in a cohort of 60 patients divided in three equal groups (healthy, gingivitis, and periodontitis), the concentration of GCF and serum interleukin (IL) 35 was found significantly higher in the periodontitis group (Raj et al, ). The same results were found for other inflammatory markers, such as visfatin, vascular endothelial growth factor (VEGF), oncostatin M, protein carbonyl, and tumor necrosis factor α (TNF‐α).…”
Section: Introductionmentioning
confidence: 99%
“…Another study also demonstrated that IL-35 in GCF and serum of CP patients was significantly higher than that in the control group [41]. Non-surgical periodontal therapy correspondingly decreased the IL-35 level in GCF compared with untreated CP patients [42], suggesting an important role of IL-35 in chronic inflammation of CP. However, IL-35 and periodontal clinical indicators have been correlated negatively [43].…”
Section: Discussionmentioning
confidence: 93%
“…IL-35, a member of the IL-12 family, is an anti-inflammatory cytokine responsible for immune system maintenance, leading to Treg expansion and Th17 cell inhibition [37]. IL-35 is not constitutively expressed in human tissue, but it is produced in response to inflammatory stimuli [38], such as periodontitis.…”
Section: Discussionmentioning
confidence: 99%